MULTIMEDIA APPLICATION FOR FACILITY INFORMATION ON CASSETTE TRAND'S MUSIC STORES USING MACROMEDIA FLASH 8 - Nicholas Ardiansyah; Rahayu Noveandini, SKom, MMSI (Jurnal Sistem Informasi, 2010)
Interesting development of the computer with the various trends that have increasedas never stopped. One thing that this trend is about the use of multimedia, where tocreate a multimedia application programs in search of songs - songs that not onlylisten but can see the songs that we choose to use as a means of information hasattracted the attention of society at a record store that is "Shop Cassette Trend's Music".